Effects of coffee consumption on subclinical inflammation and other risk factors for type 2 diabetes: a clinical trial - Kempf, Kerstin; Herder, Christian; Erlund, Iris; Kolb, Hubert; Martin, Stephan; Carstensen, Maren; Koenig, Wolfgang; Sundvall, Jouko; Bidel, Siamak; Kuha, Suvi; Tuomilehto, Jaakko (The American journal of clinical nutrition, 2010)
Coffee consumption is associated with a decreased risk of type 2 diabetes. Suggested mechanisms underlying the association have included attenuation of subclinical inflammation and a reduction in oxidative stress. The aim was to investigate the effects of daily coffee consumption on biomarkers of coffee intake, subclinical inflammation, oxidative stress, glucose, and lipid metabolism. Habitual coffee drinkers (n = 47) refrained for 1 mo from coffee drinking; in the second month they consumed 4 cups of filtered coffee/d and in the third month 8 cups of filtered coffee/d (150 mL/cup). Blood samples were analyzed by gas chromatography-mass spectrometry, bead-based multiplex technology, enzyme-linked immunosorbent assay, or immunonephelometry. Coffee consumption led to an increase in coffee-derived compounds, mainly serum caffeine, chlorogenic acid, and caffeic acid metabolites. Significant changes were also observed for serum concentrations of interleukin-18, 8-isoprostane, and adiponectin (medians: -8%, -16%, and 6%, respectively; consumption of 8 compared with 0 cups coffee/d). Serum concentrations of total cholesterol, HDL cholesterol, and apolipoprotein A-I increased significantly by 12%, 7%, and 4%, respectively, whereas the ratios of LDL to HDL cholesterol and of apolipoprotein B to apolipoprotein A-I decreased significantly by 8% and 9%, respectively (8 compared with 0 cups coffee/d). No changes were seen for markers of glucose metabolism in an oral-glucose-tolerance test. Coffee consumption appears to have beneficial effects on subclinical inflammation and HDL cholesterol, whereas no changes in glucose metabolism were found in our study. Furthermore, many coffee-derived methylxanthines and caffeic acid metabolites appear to be useful as biomarkers of coffee intake.